Cytotoxic Effects of Extract and Fractions of African Leaves (Vernonia amygdalina Delile.) Against WiDr Cells - Ezra Simanjuntak; Denny Satria; Poppy Hasibuan (Jurnal FARMASIMED (JFM), 2026)
Background: Colon cancer remains a major unresolved health problem worldwide, ranking as the third leading cause of death. African leaf (Vernonia amygdalina) is one of the plants widely used in traditional medicine. Several studies have identified phytoconstituents, including flavonoids, sesquiterpene lactones, and bactericidal saponins, with diverse pharmacological properties, including anticancer effects. Objective: This study aimed to determine cytotoxic activity of the extract and fraction of African leaf against WiDr cells. Method: African leaf extract was produced by reflux extraction with methanol, then fractionated using n-hexane, chloroform, and ethyl acetate. The analysis of total flavonoid and phenolic contents was carried out using a colorimetric method with AlCl3 and Folin-Ciocalteu reagent. Antioxidant activity was assessed using the DPPH method. Cytotoxic activity was tested using the MTT method against WiDr cells. Then, the data were analysed using the IC50 value. Results: The cytotoxicity test shows that the chloroform fraction has the strongest activity, with an IC50 value of 78.45 ± 8.95 μg/mL, followed by the n-hexane fraction of (119.07 ± 3.98 μg/mL), ethyl acetate fraction of (126.39 ± 3.28 μg/mL), methanol extract of (430.70 ± 31.92 μg/mL), and water fraction of (1607.71 ± 89.85 μg/mL). Conclusion: The chloroform fraction of African leaves shows strong cytotoxic activity against WiDr cells.